2020
DOI: 10.3389/fphys.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pectoralis Major Muscle Satellite Cell Population Heterogeneity, Macrophage Density, and Collagen Infiltration in Broiler Chickens Affected by Wooden Breast

Abstract: Muscle satellite cells (MSCs) are myogenic stem cells that play a critical role in posthatch skeletal muscle growth and regeneration. Activation of regeneration pathways to repair muscle fiber damage requires both the proliferation and differentiation of different MSC populations as well as the function of resident phagocytic cells such as anti-inflammatory and pro-inflammatory macrophages. The Wooden Breast (WB) phenotype in broiler chickens is characterized by myofiber degeneration and extensive fibrosis. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In agreement with the on-going regenerative process in the presence of WB myopathy, numbers of total nuclei and mitotically active satellite cells were increased in the 43 day broilers compared with those of non-WB ( Meloche et al, 2018 ). However, the mitotic activity of the satellite cell population was significantly altered in WB broiler, suggesting the compromised reparative capacity of the satellite cells in the abnormal birds ( Ferreira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the on-going regenerative process in the presence of WB myopathy, numbers of total nuclei and mitotically active satellite cells were increased in the 43 day broilers compared with those of non-WB ( Meloche et al, 2018 ). However, the mitotic activity of the satellite cell population was significantly altered in WB broiler, suggesting the compromised reparative capacity of the satellite cells in the abnormal birds ( Ferreira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Affected breasts can also exhibit bulging and pale areas that can be associated with the presence of exudate and hemorrhage in severely affected fillets (Barbut, 2019). Wooden breast can be classified as mild, moderate or severe and different degrees of this myopathy have been reported in many countries where fast-growing broiler chickens are raised (Kuttappan et al, 2012a;Sihvo et al, 2014;Cruz et al, 2017;Ferreira et al, 2020). Recent industry reports have suggested that about 20% of the breast fillets are affected by WB, although a wide range of incidence has been reported in different flocks and studies (as reviewed by Barbut, 2019 andPetracci et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As revealed by the immunohistochemistry staining, PAX7 + proliferation density was signi cantly compromised by AD feeding. With this data, we could extrapolate that decreased PAX7 + density resulted in poor muscular differentiation and repair activities during the later phase of AD birds that caused hypertrophic muscle defects (41,44). From the histology standpoint, IF might contribute to normal muscle growth essential for optimal muscular cell proliferation, maintenance, and repair during broiler production.…”
Section: Discussionmentioning
confidence: 96%